Influencia temporal de los intangibles en el desempeño económico y de mercado - Ferrari, Angélica (2023)
The capacity of intangible assets to generate persistent economic and market performance in organizations is still controversial in the accounting literature. In stronger economies this strategic role seems to be clearer, however, in developing economies, this is not much debated and little is known from an empirical standpoint. Given this, this study aims to analyze the influence of the intangibility index on economic and market performance. The research population is formed by Brazilian companies listed on the Brasil, Bolsa e Balcão (B3), whose data were collected in the Refinitiv Eikon database for the period from 2010 to 2019, making up a final sample of 148 Brazilian companies, totaling 1,148 observations. For the data analysis, multiple linear regressions were conducted with specification by robust errors, whose results indicate that the intangible assets of Brazilian listed companies positively influence the market performance, but the same does not occur for the economic performance, which presented a negative statistical relation.